Risk Factors of Preterm Labour Thi Qar Governorate Iraq - Izdihar Nsaif Ali; Sara Salih Abdullah; Saja Kareem Kamil; Khadija Khalid Abdulhassan; Zahraa Shakir Waja’an; Mujtaba Khaleel (Academia Open, 2025)
Background: Preterm birth, defined as delivery between 24 and 37 weeks of gestation, remains a leading cause of neonatal morbidity and mortality. Specific Background: It can occur spontaneously or due to medical indications, with risk factors ranging from maternal age and infections to obstetric history. Knowledge Gap: Despite global recognition of these risks, limited data exist on the specific contributing factors in localized hospital settings within developing regions. Aims: This study aimed to identify the predominant factors associated with preterm birth among pregnant women at Bint Huda Hospital. Results: Among 80 women who experienced preterm birth, the majority were aged 20–30 years (66.3%), had primary education (70%), and lived in urban areas (55%). Urinary tract infection emerged as the most significant risk factor (82.5%), followed by premature membrane rupture (27.5%), preeclampsia (25%), and a history of previous preterm birth (25%). Most participants were multiparous (63.8%) and had received good antenatal care (85%). Cesarean section was the dominant mode of delivery (60%). Novelty: This study highlights the prominence of infections, especially urinary tract infections, over traditionally emphasized factors like maternal age or multiple gestations. Implications: The findings underscore the importance of targeted infection prevention and antenatal surveillance to reduce preterm birth rates in similar populations.Highlights: Urinary tract infection is the most prevalent risk factor. Most preterm births occurred in women with good antenatal care. Cesarean section was the leading mode of delivery. Keywords: Preterm Birth, Risk Factors, Urinary Tract Infection, Antenatal Care, Cesarean Delivery